Changes in LDL particle composition after the consumption of meals containing different amounts and types of fat. - Callow, J; Summers, L; Bradshaw, H; Frayn, K (2002)
BACKGROUND: Remodeling of lipoprotein particles in the postprandial period is considered to be an important source of atherogenic particles, but acute changes occurring after meals have been little studied. OBJECTIVE: We sought to characterize changes in LDL particle composition occurring after a single meal, with particular reference to potential lipid exchange with particles carrying dietary fatty acids. DESIGN: In a balanced design, 8 healthy subjects ingested isoenergetic meals of different fat content: low-fat, rich in saturated fatty acids (SFAs), and rich in polyunsaturated fatty acids (PUFAs). We investigated changes in LDL composition 4 and 6 h after meal ingestion. RESULTS: The LDL triacylglycerol-to-protein ratio closely mirrored the plasma triacylglycerol concentrations after each of the meals, and there was a strong association between these variables in both the fasting and postprandial states (P < 0.001). A postprandial increase in LDL triacylglycerol was associated with a decrease in LDL cholesterol. There were no effects of the ingestion of a single meal on the LDL density profiles for protein or for any of the lipid components. The fatty acid composition of total LDL lipids changed in the postprandial period, with an enrichment in PUFA after the PUFA-rich meal and in SFA after the SFA-rich meal. CONCLUSIONS: The changes observed in LDL composition after single meals are in accord with the proposition that there is neutral lipid exchange in the postprandial period, with triacylglycerol enrichment of LDL particles at the expense of cholesteryl esters. The change in the fatty acid composition of LDL particles implies significant lipid exchange with particles containing dietary fat.